Cavity-Volume Scaling Law of Quantum-Dot Metal-Cavity Surface-Emitting Microlasers - Akira Matsudaira; Chien-Yao Lu; Meng Zhang; Shun Lien Chuang; Erik Stock; Dieter Bimberg (IEEE Photonics Journal, 2012)
Quantum-dot (QD) metal-cavity surface-emitting microlasers are designed, fabricated, and characterized for various sizes of cavity volume for both lateral and vertical confinements. Microlasers using submonolayer QDs in the active region are fabricated according to our design model optimized for a resonant metal cavity. The cavity-volume scaling law is studied by our theoretical modeling and experimental demonstration. The smallest laser has a diameter of 1 <tex Notation="TeX">$μ\hbox{m}$</tex> with silver metal cladding operating at room temperature with electrical injection in pulsed mode. Our experimental results show significant self-heating effect in the smaller devices with a diameter of a few micrometers due to high series resistance and high threshold gain. With the use of hybrid metal-DBR mirrors, the number of DBR pairs in the top hybrid mirror can be reduced from 19.5 to 5.5 without sacrificing threshold current density.